Implementasi Teori Sosial Kognitif Albert Bandura dalam Pembelajaran Fikih di MI Al Ikhlas Pancawangi - Lilih Parlina (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The Social Cognitive Theory proposed by Albert Bandura emphasizes that learning occurs largely through the process of observation. Teachers play an important role as models who provide direct examples so that students can understand and imitate a particular action or skill. This study aims to describe the implementation of Albert Bandura's social cognitive theory through modeling strategies in Islamic Jurisprudence learning on the material